ECONOMIC FEASIBILITY AND WATER PRODUCTIVITY BY ALTERNATIVE CROPPING SEQUENCES TO SUGARCANE UNDER DIFFERENT IRRIGATION METHODS - HIRWE, N.A.; JADHAV, A.S. (Annals of Agricultural Research, 2014)
A field experiment was conducted during 2005-07 to evaluate economic feasibility and water productivity by alternative cropping sequences to sugercane under different irrigation methods at Rahuri. Drip irrigation method recorded significantly more sugarcane equivalent yield, production efficiency, economic efficiency, returns per day and returns per ha-cm of water than other irrigation methods. The adoption of brinjal-chilli sequence saved 19.89 percent water over sugarcane and significantly increased water productivity, return per rupee invested on fertilizer and irrigation than sugarcane and cotton-beet root sequence. It is concluded that, the brinjal-chilli sequence produced significantly more returns per rupee invested on fertilizer, return per day, ha-cm of water under drip irrigation. Hence, it is economically more feasible than sugarcane and cotton beet root-sequence under drip irrigation.